PREDICTORS OF EATING HABITS OF OVERWEIGHT YOUNG WOMAN IN PAKISTAN - Zainab Javed; Rafia Rafique (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research has explored the predictors of unhealthy eating habits of young overweight women.